Translation and Validation of the Italian Version of the Team-Based Learning Student Assessment Instrument (TBL-SAI) in Nursing Students - Valeria Vannini; Rosario Caruso; Sara Alberti; Sergio Rovesti; Paola Ferri (Nursing Reports)
Background/Objectives: Team-based learning is an educational strategy that promotes active learning and student engagement through structured team activities. It contrasts with traditional teaching models by emphasizing student preparation and collaboration. The TBL-SAI is a reliable and valid instrument designed to evaluate students’ attitudes towards TBL, assessing dimensions such as accountability, preference for lecture or team-based learning, and satisfaction with TBL. Validating the TBL-SAI in different languages ensures its applicability and accuracy in diverse educational contexts, supporting the global adoption of TBL methodologies. Thus far, no Italian validation of this tool has been performed. The aim of this study is to validate the Italian version of the Team-Based Learning Student Assessment Instrument (TBL-SAI) among nursing students. Methods: A methodological-driven translation process and a cross-sectional study design were used. The study was conducted from November 2022 to March 2023 and involved 202 nursing students from the University of Modena and Reggio Emilia (Italy). Convenience sampling was employed to recruit participants who had experienced at least one TBL session during the academic year 2022/2023. The validation process included translation, back-translation, and expert panel review, followed by a pilot test to ensure clarity and comprehension. Data were collected using the self-administered TBL-SAI. The responses were analyzed using Exploratory Structural Equation Modeling (ESEM) to assess the scale’s validity and McDonald’s ω to evaluate internal consistency. Results: The ESEM results supported the validity of the Italian TBL-SAI, maintaining the factor structure proposed in the original instrument. The model fit indices indicated a good fit (χ2(318) = 384.097, p = 0.0065; RMSEA = 0.032; CFI = 0.974; TLI = 0.957). McDonald’s ω values exceeded 0.70 for all factors, confirming adequate internal consistency. Conclusions: This study successfully validated the Italian version of the TBL-SAI, demonstrating its reliability and validity for assessing perceptions of TBL among Italian undergraduate nursing students. However, future studies should employ Confirmatory Factor Analysis to further test the proposed factor structure and explore the instrument’s applicability in various educational settings. The validated TBL-SAI is recommended for use in evaluating students’ attitudes towards TBL, providing actionable feedback for educators to improve teaching methods and integrate TBL methodologies effectively.